Drosophila windpipe codes for a leucine-rich repeat protein expressed in the developing trachea. - Huff, J.L.; Kingsley, K.L.; Miller, J.M.; Hoshizaki, D.K. (Mechanisms of Development, 2002)
The embryonic tracheal system of Drosophila provides an important model for understanding the process of epithelial branching morphogenesis. Here we report the sequence and expression analysis of a novel tracheal gene, named windpipe (wdp). wdp is identical to the predicted gene CG3413 and encodes a transmembrane, leucine-rich repeat family member. wdp transcripts appear abruptly at stage 15 and are restricted to primary tracheal branches that give rise to secondary branches.